2021
DOI: 10.1371/journal.pone.0248333
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of non-neoplastic epithelium that appears within gastric cancer with and without Helicobacter pylori eradication: A retrospective study

Abstract: A non-neoplastic epithelium (NE) often appears in gastric cancer (GC). We explored the histological features of NE in comparison between HP-eradicated and HP-infected GCs. We enrolled 40 HP-eradicated and 40 HP-infected GCs matched by size, macroscopic and histological type. NE was classified into full gland type and surface type; the former was a non-neoplastic gland isolated within cancer, and the latter was NE on the surface of the cancer. Surface type was additionally divided into NE at the cancer margin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Next, according to the location and structure, NE was classified into full gland, marginal surface and internal surface types. Noda et al [33] found that only internal surface type was significantly linked to H pylori -eradicated cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, according to the location and structure, NE was classified into full gland, marginal surface and internal surface types. Noda et al [33] found that only internal surface type was significantly linked to H pylori -eradicated cancer.…”
Section: Resultsmentioning
confidence: 99%
“…[64] The findings demonstrate that NBI-ME has significantly superior diagnostic accuracy to WLE for gastric cancer after H pylori eradication, especially for lesions with a “gastritis-like” appearance. [33,65] Furthermore, blue laser imaging (BLI) is a new image-enhanced endoscopy technique that uses laser illumination to change brightness and contrast. [66,67] BLI has improved diagnostic performance for lesions compared with NBI in brightness and contrast.…”
Section: Discussionmentioning
confidence: 99%
“…About 60% of gastric cancer patients from developed countries, and 75% of patients with gastric cancer from developing countries suffer from chronic H. pylori infection ( Park et al, 2021 ). Chronic gastritis caused by H. pylori infection results in the release of pathogenic factors such as urease, vacuolar toxin A, CagA protein, inflammatory mediators, and reactive oxygen species metabolites, which lead to abnormal proliferation and apoptosis of gastric mucosal epithelial cells, resulting in gastric cancer ( Noda et al, 2021 ). Although recent progress with antibiotics and other drugs has been made in treating H. pylori infection, it remains an important factor in increasing the incidence of gastric cancer ( Ding, 2020 ).…”
Section: Discussionmentioning
confidence: 99%